The CoronaSurveys System for COVID-19 Incidence Data Collection and Processing - Baquero, Carlos; Casari, Paolo; Fernandez Anta, Antonio; García-García, Amanda; Frey, Davide; Garcia-Agundez, Augusto; Georgiou, Chryssis; Girault, Benjamin; Ortega, Antonio; Goessens, Mathieu; Hernández-Roig, Harold A.; Nicolaou, Nicolas; et al. (Frontiers in Computer Science, 2021)
CoronaSurveys is an interdisciplinary scientific initiative with the objective of devising a system to infer the incidence of COVID-19 around the world using anonymous open surveys. The surveys have been translated in 60 languages and are continuously collecting participant responses from any country in the world. The responses collected are pre-processed, transformed and stored in a version-controlled repository, which is publicly available to the scientific community. In addition, the CoronaSurveys team has devised several estimates computed based on survey responses and other data, and makes them available on the project's website in the form of tables, as well as interactive plots and maps. In this paper, we present and describe the computational system developed for the CoronaSurveys project. It consists of elements and processes interconnected in a non-trivial form. Among others, these include the web survey, the mobile apps, the cleaning and aggregation process of the survey responses, the process of storage and publication of the data, the processing of the data and the computation of estimates, and the visualization of the results.